THE NEEDS OF TEACHING ENGLISH PHONOLOGY IN HIGHER EDUCATION - Evi Kasyulita (English Study Program University of Pasir Pengaraian, 2017)
The research aimed to analyze students’ need to learn English phonology at fifth semester students of English Study Program of University of Pasir Pengaraian. Phonology is one of lessons that difficult to learn, because the students must concentrate and focus to learn it. To make students more understand in learning English phonology, the researcher need to know what students feeling before studying phonology and what their wish in learning it. Because of that reason, the researcher tried to analyze students’ need in English phonology. There were two types of instrument to gather the data; questionnaire and interview. The total students in this research are 42 students, which consist of 22 students in class A, and 20 students in class B. The researcher analyzed students answer based on interview. The finding was students need lecturer to be patient to teach them in English phonology, the students need the lecturer explain topic per topic in slowly until they understood, the students need more practice or exercise than theory or discussion.